Energy Access in Mountain Arba Hill, Jango Village From The Perspective of Community Environmental Justice - Herdianto, Tedi; Wahyuningsih, Olyvia; Fatimah, Riky; Azzahra, Adelia (Ridwan Institute, 2024)
Environmental justice from the perspective of public participation in the development of natural resources is a national program where the government is starting to switch from fossil energy to green energy, which means that in the future the government will no longer hope for energy such as coal, oil and gas, etc. This is a very strategic step taken by the government. Centralized policies are the antithesis of the increasing pressure to decentralize regional government, including regarding the management of natural resources (SDA) in the mining and oil and gas sectors, To ensure that this program runs well, of course the community is involved in monitoring it. Community participation in sustainable development is indeed weak, including in terms of policy making, even though the laws and regulations also stipulate that the community has rights as explained in the Aarhus Convention, where parties have an obligation to guarantee the rights of access to information, community participation in decision making, and access to justice in environmental matters in accordance with the provisions of the convention. Then in Law No. 32 of 2009 concerning Environmental Protection and Management, it is intended, among other things, 1) to provide information to the government, 2) to increase the public's willingness to accept government decisions. 3) Helps with legal protection. and 4) Democratize decision making. From the above basis, it further strengthens the community so that it can participate actively in the development of natural resources in this country.